Styles and Behavior in Slow Tourism for Senior Tourists in the Thai Western Region - Sungrugsa, Narin; Plomelersee, Supaporn; Warabamrurngkul, Theerangkoon (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aimed to 1) study behaviors, attitude, motivation and demand for slow tourism for senior tourists in the Thai western region, 2) analyze a the model of motivation in the slow tourism as mentioned above, and 3) propose guidelines for the management of slow tourism. Based on the methodology of action research, the research process was divided into three stages. Both Thai and foreign tourists, totally 400 persons were included in this study by using the accidental sampling technique. The research instruments were a general questionnaire, a questionnaire for endorsement of the model for motivation, guidelines for in-depth interviews and focus group discussions. The collected data was quantitatively and qualitatively analyzed and presented through frequency, percentage, mean, standard deviation, t-test, F-test, LSD, Pearson’s product-moment correlation coefficient and its content analysis, respectively. The results were as follows: regarding tourism behavior, the Thai and foreign tourists (43.50%) would seek and get the information data from internet sources, and 78.00% of them would aim to relax and tour for the trip. By and large they would travel with their friends (46.25%) and the time periods spent on one trip were longer than 5-7 days (75.73%). The number of trips in the four western Thai provinces was one time (44.80%). Most of them (86.25%) would stay with householders, or the so-called homestay tourism, and they would stay more than three days (67.00%), Nearly half of them (46%) would spend more than 5,000 Baht. Their overall attitude, satisfaction and motivation toward tourism were at the highest level. Furthermore, the model of tourism was produced and named the "1202T2A2 Model", and this was endorsed. Guidelines for slow tourism management were presented for 1) State Sector: the government offices should manage the tourism with quality approaches, arrange facilities for senior groups, develop quality in tourist services leading to an impressive and safe tourism, 2) Private Sector: the entrepreneurs should deal honestly in business and not exploit their customers, help to develop tourism and arrange tourist activities suitable for seniors groups, 3) Community and Local sector: should take care of the tourist sites, continuously support tourism, improve basic infrastructure and facilities for the elderly,and develop new tourism sites.